Internal gastric fistula, as a complication of Roux gastric shunting procedure, performed for morbid obesity - A. V. Fomin; A. S. Lavrik; D. Sh. Makhatadze; I. P. Beskrovniy; A. S. Serhiieva; M. N. Maiorenko (Клінічна хірургія, 2020)
Internal gastric fistula, as a complication of Roux gastric shunting procedure, performed for morbid obesity